STRUKTUR KOMUNITAS PLANKTON DI DANAU BATUR, KECAMATAN KINTAMANI, PROVINSI BALI - Sipayung, Rista Hotdelina; Putri Wijayanti, Ni Putu; Wiweka Krisna Dewi, Ayu Putu (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 18 No 2 (2024), 2024)
Plankton is the most important component of aquatic life and plays an important role in the food chain. Plankton is divided into two, namely animal plankton called zooplankton and plant plankton called phytoplankton. This research aims to determine the plankton community structure and water quality parameters in Lake Batur, Kintamani District, Bali Province. The research was conducted in January-March 2024 at Lake Batur. The research method used was a quantitative descriptive method. The sampling technique used was the purposive sampling method. The identification results show that there are 4 classes of phytoplankton, namely Bacillariophyceae, Cyanophyceae, Euglenophyceae and Chlorophyceae. The phytoplankton abundance value is in the range of 1.943-6.568 ind/L, the average diversity index value is 1.030, the average uniformity index value is 0.391, the average dominance index value is 0.461 so it is included in oligotrific and mesotrific waters. The results of zooplankton observations found 4 classes containing 5 genera, namely Branchiopoda, Ostracoda, Maxillopoda and Lobosea. The average value of zooplankton abundance ranges from 35-145 ind/L, the average value of the zooplankton diversity index is 1.388, the average value of the zooplankton uniformity index is 0.863, the average value of the zooplankton dominance index is 0.289, so it is included in the mesotrophic waters category. The results of observations of chemical and physical parameters obtained an average value of temperature of 27-28 o C, brightness of 4-5 m, pH of 8.5, DO of 6.53-6.73 mg/L, nitrate of 0.41- 0.938 mg/L, and phosphate, namely 0.705-0.111 mg/L. The water quality conditions in Lake Batur show that the waters are still suitable for plankton growth. Keywords: Lake Batur; Water quality; Plankton Community Structure